Effect of 12-Month Resistance Training on Changes in Abdominal Adipose Tissue and Metabolic Variables in Patients with Prediabetes: A Randomized Controlled Trial. (16th October 2019) - Yan, Juan; Dai, Xia; Feng, Jitao; Yuan, Xiaodan; Li, Jianing; Yang, Lihong; Zuo, Panpan; Fang, Zhaohui; Liu, Chao; Hsue, Cunyi; Zhu, Junya; Miller, Joshua D.; et al.
Abstract : Objective . To examine the effects of resistance training relative to aerobic training on abdominal adipose tissue and metabolic variables in adults with prediabetes. Methods . 105 participants with prediabetes were randomized into the resistance training group (RT, n = 35 ), aerobic training group (AT, n = 35 ), and control group (CG, n = 35 ). The participants completed supervised 12-month exercise; the control group followed the primary lifestyle without exercise intervention. The primary outcomes were visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) measured by computed tomography (CT). Secondary outcomes were body composition, lipid profile, and metabolic variables. Results . A total of 93 participants completed the study. There were nonsignificant differences between groups before intervention. After training, VAT decreased significantly in AT and RT compared with CG (P = 0.001 andP = 0.014, respectively). Although no significant difference in SAT was found across groups, SAT decreased significantly over time within each exercise group (allP = 0.001 ). Increase in muscle mass was greater in RT than that in AT and CG (P = 0.031 andP = 0.045, respectively). Compared with CG, fasting plasma glucose (FPG) decreased significantly in RT and AT (P = 0.003 andP = 0.014, respectively). There was a significant difference in the number of prediabetes who converted to diabetes among AT and RT, as compared with the control group (P = 0.031 andP = 0.011, respectively). No significant differences were observed in lipid, waist-to-hip ratio (WHR), body mass index (BMI), fasting insulin (FI), 2-hour postprandial glucose (2hPG), glycosylated hemoglobin (HbA1c), HOMA-IR, and HOMA- β across groups. Conclusion . Both aerobic training and resistance training are effective in reducing abdominal adipose tissue and fasting plasma glucose in adults with prediabetes. Importantly, resistance training but not aerobic training is effective in augmenting muscle mass. Trial Registration . The trial is registered withNCT02561377 (date of registration: 24/09/2015).